SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Discovery of imbricated beachrock deposits adjacent to the Java trench, Indonesia: influence of tsunami and storm waves, and implications for mega-thrust earthquakes - R. Harris; W. Meservy; H. Sulaeman; M. Bunds; J. Andreini; B. Sharp; B. Berrett; J. Whitehead; G. Carver; G. Setiadi; S. Hapsoro; C. Prasetyadi (Natural Hazards, 2024)

Systematic review of pharmacological treatments that reduce conditioned taste aversions in rodents: A potential animal model of pediatric feeding disorder and avoidant/restrictive food intake disorder (ARFID) - Marise B. Parent; Kathryn E. Whitley; Usama Zafar; Hana F. Zickgraf; William G. Sharp (Appetite, 2024)

Uncertainty sources for measurable ocean carbonate chemistry variables - Brendan R. Carter; Jonathan D. Sharp; Andrew G. Dickson; Marta Álvarez; Michael B. Fong; Maribel I. García‐Ibáñez; Ryan J. Woosley; Yuichiro Takeshita; Leticia Barbero; Robert H. Byrne; Wei‐Jun Cai; Melissa Chierici; et al. (Limnology and Oceanography, 2024)
The ocean carbonate system is critical to monitor because it plays a major role in regulating Earth's climate and marine ecosystems. It is monitored using a variety of measurements, and it is commonly understood that all components of seawater carbonate chemistry can be calculated when at least two carbonate system variables are measured. However, several recent studies have highlighted systematic discrepancies between calculated and directly measured carbonate chemistry variables and these discrepancies have large implications for efforts to measure and quantify the changing ocean carbon cycle. Given this, the Ocean Carbonate System Intercomparison Forum (OCSIF) was formed as a working group through the Ocean Carbon and Biogeochemistry program to coordinate and recommend research to quantify and/or reduce uncertainties and disagreements in measurable seawater carbonate system measurements and calculations, identify unknown or overlooked sources of these uncertainties, and provide recommendations for making progress on community efforts despite these uncertainties. With this paper we aim to (1) summarize recent progress toward quantifying and reducing carbonate system uncertainties; (2) advocate for research to further reduce and better quantify carbonate system measurement uncertainties; (3) present a small amount of new data, metadata, and analysis related to uncertainties in carbonate system measurements; and (4) restate and explain the rationales behind several OCSIF recommendations. We focus on open ocean carbonate chemistry, and caution that the considerations we discuss become further complicated in coastal, estuarine, and sedimentary environments.

Exposure to global change and microplastics elicits an immune response in an endangered coral - Colleen B. Bove; Katharine Greene; Sharla Sugierski; Nicola G. Kriefall; Alexa K. Huzar; Annabel M. Hughes; Koty Sharp; Nicole D. Fogarty; Sarah W. Davies (Frontiers in Marine Science, 2023)
Global change is increasing seawater temperatures and decreasing oceanic pH, driving declines of coral reefs globally. Coral ecosystems are also impacted by local stressors, including microplastics, which are ubiquitous on reefs. While the independent effects of these global and local stressors are well-documented, their interactions remain less explored. Here, we examine the independent and combined effects of global change (ocean warming and acidification) and microplastics exposures on gene expression (GE) and microbial community composition in the endangered coral Acropora cervicornis . Nine genotypes were fragmented and maintained in one of four experimental treatments: 1) ambient conditions (ambient seawater, no microplastics; AMB); 2) microplastics treatment (ambient seawater, microplastics; MP); 3) global change conditions (warm and acidic conditions, no microplastics; OAW); and 4) multistressor treatment (warm and acidic conditions with microplastics; OAW+MP) for 22 days, after which corals were sampled for genome-wide GE profiling and ITS2 and 16S metabarcoding. Overall A. cervicornis GE responses to all treatments were subtle; however, corals in the multistressor treatment exhibited the strongest GE responses, and genes associated with innate immunity were overrepresented in this treatment. ITS2 analyses confirmed that all coral were associated with Symbiodinium ‘fitti’ and 16S analyses revealed similar microbiomes dominated by the bacterial associate Aquarickettsia , suggesting that these A. cervicornis fragments exhibited remarkably low variability in algal and bacterial community compositions. Future work should focus on functional differences across microbiomes, especially Aquarickettsia and viruses, in these responses. Overall, results suggest that when local stressors are coupled with global change, these interacting stressors present unique challenges to this endangered coral species.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Functional convergence of microbes associated with temperate marine sponges - M. Ribes; E. Jiménez; G. Yahel; P. López‐Sendino; B. Diez; R. Massana; J. H. Sharp; R. Coma (Environmental Microbiology, 2012)
Summary Most marine sponges establish a persistent association with a wide array of phylogenetically and physiologically diverse microbes. To date, the role of these symbiotic microbial communities in the metabolism and nutrient cycles of the sponge‐microbe consortium remains largely unknown. We identified and quantified the microbial communities associated with three common Mediterranean sponge species, Dysidea avara , Agelas oroides and Chondrosia reniformis ( Demospongiae ) that cohabitate coralligenous community. For each sponge we quantified the uptake and release of dissolved organic carbon (DOC) and nitrogen (DON), inorganic nitrogen and phosphate. Low microbial abundance and no evidence for DOC uptake or nitrification were found for D. avara . In contrast A. oroides and C. reniformis showed high microbial abundance (30% and 70% of their tissue occupied by microbes respectively) and both species exhibited high nitrification and high DOC and NH 4 + uptake. Surprisingly, these unique metabolic pathways were mediated in each sponge species by a different, and host specific, microbial community. The functional convergence of microbial consortia found in these two sympatric sponge species, suggest that these metabolic processes may be of special relevance to the success of the holobiont.

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

Self-administration in rats allowed unlimited access to nicotine - James D. Valentine; Jonathan S. Hokanson; Shannon G. Matta; B. M. Sharp (Psychopharmacology, 1997)

Influenza infection in humans and pigs in southeastern China - N. Zhou; S. He; T. Zhang; W. Zou; L. Shu; G. B. Sharp; R. G. Webster (Archives of Virology, 1996)